An overview and impact assessment of OSHA large dairy local emphasis programs in New York and Wisconsin. Issue 8 (21st June 2018) - Liebman, Amy; Franko, Eileen; Reyes, Iris; Keifer, Matthew; Sorensen, Julie
Abstract : Background: Farming has been exempted from most labor regulations and shielded from regulatory scrutiny by the Occupational Safety and Health Administration (OSHA). Yet, agriculture and dairy in particular, has relatively high injury and fatality rates. Methods: A recent shift in OSHA's approach to agricultural worker safety and health includes two dairy‐focused Local Emphasis Programs (LEPs), one launched in Wisconsin in 2011 and the other in New York in 2014. We examine data from LEP‐related, OSHA consultations and inspections as well as non‐governmental audit programs, and review farmer perceptions about the LEP. Results: Inspections conducted by OSHA and private consultation programs highlight the presence and variety of hazards on dairy farms in Wisconsin and New York. Conclusion: The LEPs helped raise dairy producers' awareness of inherent hazards and methods to correct them. Farmers cited the LEP as beneficial, identifying it as a catalyst to reduce hazards on their farms.